Issues and current applications of interspecies extrapolation of carcinogenic potency as a component of risk assessment. - Visek, W J (1988)
The Life Sciences Research Office (LSRO) of the Federation of American Societies for Experimental Biology (FASEB) is conducting this symposium under contract with the Center for Food Safety and Applied Nutrition (CFSAN) of the Food and Drug Administration (FDA). The FDA has requested information on the strengths and weaknesses of current interspecies extrapolation methods using metabolic and pharmacokinetic data, identity of data for these methods, bases for choice of extrapolation method and selection of data base, validity and uniformity of interspecies extrapolation from target organ data, and nature and completeness of supporting data. Definitions and basic concepts of dose scaling are addressed and questions regarding appropriate units of measurement (e.g., mg/kg body weight, mg/m3 respired air, mg/m2 surface area) are raised. The use of DNA damage as a marker or end point upon which to scale carcinogenic potency is considered. Genotoxic mechanisms of carcinogenesis are emphasized because the roles of DNA adducts and DNA repair processes in initiation and promotion are much better defined than the mechanism for nongenotoxic carcinogenesis. The problems encountered in evaluating the human carcinogenicity of trichloroethylene are reviewed. The broad objectives of the symposium are discussed and the development of a structured format for the presentation of invited papers is presented.